Richard Eberhart - American Writers 55 : University of Minnesota Pamphlets on American Writers - Mills, Ralph J. (Book collections on Project MUSE., 1966)
Richard Eberhart - American Writers 55 was first published in 1966. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.